A new advanced manufacturing technology model for small, medium enterprise food industry - Mohd Asaad, Mohd Norhasni; Taib, Che Azlan; Ahmad, Mohd Akhir; Iteng, Rosman (IRAJ, 2020)
Globalisation of markets, the knowledge economy, e-business and introduction of new technologies pose new challenges to all organisations irrespective of their size and sector for sustaining their competitiveness. In this scenario successful implementation of Advanced Manufacturing Technologies (AMT) by firms can give them an edge over their competitors. It's in line with the report of Malaysian Investment Development Authority (MIDA), AMT in processing technology has widened the usage of local raw materials, expanding the range of products and increasing the investment absorbing capacity in the food industry. Most of the previous researches are conducted in measuring the impact AMT and organisation performance and limited research considering the impact towards sustainability. It was also noted the finding from previous researched are inconclusive between AMT and organisational performance. Hence, this study attempt to investigate the relationship between the AMT and organisational sustainability. Currently there are many discussions about the influence of Industrial Revolution 4.0 towards organisations, but not many studies in the food industry. Therefore, this study attempts to investigate the influence of IR 4.0 towards the relationship between the AMT and organisational sustainability in the food industry. Beside the identified gaps above, this study also attempt to measure the level of AMT implementation in the food industry among Small Medium Enterprise (SMEs) which limited research has conducted on this issue. This study will develop AMT for the food industry model. It‟s helping SMEs transition towards greater sustainability in IR4.0.